Carbon stocks and fluxes in reforestated sites of Durango, Mexico - Návar Cháidez, José de Jesús; González, Nicolás; Graciano, José (Instituto de Ecología, A.C., 2016)
In this research, we present predictions of carbon sequestration by pines growing in reforested sites of Durango, Mexico. Four methodologies to predict carbon stocks in standing aboveground biomass were tested. Two models at the whole stand scale and two hybrid models between whole stand, stand class, and individual trees were fitted. A chronosequence of 23 small-scale reforested sites and stem analysis conducted on 60 trees were used to fit model parameters and estimate goodness of fit statistics. A stand class model produced a better fit to measure carbon stocks in aboveground standing biomass. 3 Reforested sites with native pine species are sequestering carbon at differential rates partially explained by density, species, micro site, climate and age of pines. Society is benefiting from the environmental services provided by carbon sequestration and conservation of native coniferous forests.